Acute Calcium Pyrophosphate Arthritis after Parathyroidectomy - Alper Uçkun; Naciye Füsun Toraman; Tuncay Çakır; İlhan Sezer (Türk Osteoporoz Dergisi, 2017)
Hypocalcemia after parathyroidectomy is a well-known metabolic sequela, but rare conditions such as acute calcium pyrophosphate (CPP) arthritis can be observed. In this study, we presented a case of acute CPP arthritis in both knees after parathyroidectomy. A 48-year-old man presented with pain and swelling in his right knee that started 1 day ago. There was no feature in his background and family history other than parathyroidectomy surgery performed for parathyroid adenomy a week ago. The diagnosis of acute CPP arthritis was made on the basis of blood, imaging and synovial fluid analysis. Evaluation was made after 3 days and acute arthritis in left knee was detected. Similar findings were also observed in the synovial fluid examination. After cold application and colchicine 1 mg/day started, improvement in arthritis and acute phase markers was detected. Acute CPP arthritis after parathyroidectomy is a rare condition and there are various theories in this regard. According to the most widely accepted theory; as a result of the decrease in the calcium level, the solubility of the CPP crystals decreases, and the CPP crystals previously deposited in the articular cartilage are poured into the synovial fluid. As a result; CPP arthritis should also be considered in differential diagnosis in patients with arthritis after parathyroidectomy and synovial fluid analysis should be performed.